Effects of a 10-week musical instrument training on cognitive function in healthy older adults: implications for desirable tests and period of training - Wang, Xueyan; Soshi, Takahiro; Yamashita, Masatoshi; Kakihara, Marcelo; Tsutsumi, Takanobu; Iwasaki, Shoko; Sekiyama, Kaoru (Frontiers in Aging Neuroscience, 2023)
Introduction Previous studies have shown that musical instrument training programs of 16 or more weeks improve verbal memory (Logical Memory Test delayed recall), processing speed (Digit Symbol Coding Test), and executive function (Trail Making Test Part B) of musically untrained healthy older adults. However, it is unclear whether shorter-period instrument training can yield similar effects. We sought to (1) verify those results and (2) clarify if intervention effects could be detected using other measures such as reaction time. Methods Healthy older adults (mean age = 73.28 years) were pseudo-randomly assigned to an untrained control group (n = 30) or an intervention group (n = 30) that received a weekly 10-session musical instrument training program (using melodica). We conducted neuropsychological tests on which intervention effects or association with musical training were reported in previous studies. We newly included two reaction time tasks to assess verbal working memory (Sternberg task) and rhythm entrainment (timing task). Intervention effects were determined using a “group × time” analysis of variance (ANOVA). Results The intervention effects were detected on the reaction time in Sternberg task and phonological verbal fluency. Although intervention effects had been reported on Logical Memory test, Digit Symbol Coding Test and Trail Making Test in previous studies with longer training periods, the present study did not show such effects. Instead, the test-retest practice effect, indicated by significant improvement in the control group, was significant on these tests. Discussion The present results indicated the usefulness of working memory assessments (Verbal Fluency Test and Sternberg task) in detecting the effects of short-term melodica training in healthy older adults. The practice effect detected on those three tasks may be due to the shorter interval between pre- and post-intervention assessments and may have obscured intervention effects. Additionally, the findings suggested the requirement for an extended interval between pre- and post-tests to capture rigorous intervention effects, although this should be justified by a manipulation of training period.